Biosynthesis of Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) From Glucose by Escherichia coli Through Butyryl-CoA Formation Driven by Ccr-Emd Combination - Saito, Shu; Imai, Ryu; Miyahara, Yuki; Nakagawa, Mari; Orita, Izumi; Tsuge, Takeharu; Fukui, Toshiaki (Frontiers in Bioengineering and Biotechnology, 2022)
Poly((R)-3-hydroxybutyrate-co-(R)-3-hydroxyhexanoate) [P(3HB-co-3HHx)] is a practical kind of bacterial polyhydroxyalkanoates (PHAs). Previous study has established an artificial pathway for the biosynthesis of P(3HB-co-3HHx) from a structurally unrelated sugars in Ralstonia eutropha, in which crotonyl-CoA carboxylase/reductase (Ccr) and ethylmalonyl-CoA decarboxylase (Emd) are a key combination for generation of butyryl-CoA and the following chain elongation. This study focused on install of the artificial pathway into Escherichia coli. The recombinant strain of E. coli JM109 harboring 11 heterologous genes including Ccr and Emd produced P(3HB-co-3HHx) composed of 14 mol% 3HHx with 41 wt% of dry cellular weight from glucose. Further investigations revealed that the C6 monomer (R)-3HHx-CoA was not supplied by (R)-specific reduction of 3-oxohexanoyl-CoA, but by (R)-specific hydration of 2-hexenoyl-CoA formed through reverse -oxidation after the elongation from C4 to C6. While, contribution of the reverse -oxidation to conversion of the C4 intermediates was very limited, thus crotonyl-CoA, a precursor of butyryl-CoA, was generated by dehydration of (R)-3HB-CoA. Several modifications previously reported for inforcement of bioproduction in E. coli were examined for the copolyester synthesis. Elimination of global regulator Cra or PdhR as well as block of acetate formation resulted in poor PHA synthesis. The strain lacking RNase G accumulated more PHA but with almost no 3HHx unit. Introduction of phosphite oxidation system for regeneration of NADPH led to copolyester synthesis with higher cellular content and higher 3HHx composition by two-stage cultivation with phosphite when compared to that in the absence of phosphite.